Contribution of Obstructive Sleep Apnoea to Cognitive Functioning of Males With Coronary Artery Disease: A Relationship With Endocrine and Inflammatory Biomarkers - Kazukauskiene, Nijole; Fineberg, Naomi A.; Podlipskyte, Aurelija; Bunevicius, Adomas; Linares, Nicolás Francisco Narvaez; Poitras, Marilou; Plamondon, Hélène; Pranckeviciene, Aiste; Gecaite-Stonciene, Julija; Mickuviene, Narseta; Varoneckas, Giedrius; Burkauskas, Julius (Frontiers in Neuroscience, 2022)
Introduction: Our exploratory study aimed to determine whether obstructive sleep apnoea (OSA) could affect cognitive functioning in males with coronary artery disease (CAD), and whether such impact could be associated with changes in thyroid hormones and inflammatory marker regulation on cognitive functioning. Method: We evaluated different endocrine and inflammatory biomarkers, including free triiodothyronine [fT3], free tetraiodothyronine [fT4], N-terminal pro-B-type natriuretic peptide [NT-pro-BNP], and high-sensitivity C-reactive protein [hs-CRP] serum levels in 328 males (x ̅ = 57±10 years), undergoing cardiac rehabilitation after an acute coronary event. Participants underwent full-night polysomnography and were classified in mild/non-OSA (n = 253) and OSA (n = 75) according to an apnoea-hypopnoea index ≥15 event/h. Cognitive functioning testing included the Digit Span Test, Digit Symbol Test (DSST), and Trail Making Test. Analyses of variance assessed the impact of OSA on cognitive functioning and possible relationships of fT3/fT4, NT-pro-BNP and with hs-CRP on cognitive measures. Results: Significant group (OSA, mild/non-OSA) × NT-pro-BNP (<157.0 vs. ≥157.0, ng/L) interactions were found for the DSST raw score (F2,324 =3.58, p = 0.014). Decomposition of interactions showed that the DSST scores of the OSA group with NT-pro-BNP ≥157.0 ng/L (M = 33.2; SD = 8.1) were significantly lower, p = 0.031, than those of the mild/non-OSA with NT-pro-BNP <157.0 ng/L (M = 37.7; SD = 8.9). Conclusions: These findings indicate that males with OSA and clinically elevated NT-pro-BNP levels experienced inferior psychomotor performance compared to those without OSA and reduced NT-pro-BNP levels.